Sensor capacitivo para determinação da concentração de biodiesel na mistura diesel/biodiesel - Carvalho, Christian Diniz (2016)
The use of biodiesel/diesel mixtures out of the quality standards specified by the National Agency of Petroleum and Natural Gas and Biofuels - ANP can be harmful to the environment and automotive engines. Therefore, it is important to develop methodologies capable of certifying the commercial quality of such products. In such context, this project aims to design a low-cost sensor to the quantification of the biodiesel content in biodiesel / diesel pseudo-binary blends based on the dielectric constant as a response. Thus, pseudo-binary samples were prepared using soybean or babassu methyl biodiesel with commercial diesel. The dielectric measurements were performed using a LCR meter operating in parallel circuit. In this way, a voltage of 1.0 V, frequency ranging from 100 Hz to 2000 Hz and a pitch of 100 Hz were employed. The dielectric profile of diesel and biodiesel showed remarkable variations in the frequency range of 100-300 Hz and less intense changes in under 400 and 2000 Hz, which confirms greater system stability in this measurement range. The results obtained by ANOVA of pure soybean biodiesel, pure babassu biodiesel and diesel oil showed that there was no significant difference between data treatment at the 95% significance level, once the Fcalculate was lower than the Fcritical. The frequency of 1000 Hz was adopted in biodiesel analysis of content in diesel, as it was verified that the system had a higher stability at this frequency. The correspondent values of dielectric constant demonstrate regularity and stability as well as a precision between the values found. Observing the values of the dielectric constants as a function of the percentage of biodiesel in the diesel, it was possible to plot the correlation curve for a linear model. Finally, according to the Kruskal-Wallis test reinforces the thesis that measuring dielectric constants (K) can be used to determine the concentration of biodiesel in mineral diesel.